161k views
4 votes
Solve the given equation: 2 x ( x + 3 ) − 6 ( x + 3 ) = 0 2 x ( x + 3 ) - 6 ( x + 3 ) = 0

User SyRenity
by
5.2k points

1 Answer

6 votes

Answer:

x = 3 or x = -3

Explanation:

Solve for x over the real numbers:

2 x (x + 3) - 6 (x + 3) = 0

Expand out terms of the left hand side:

2 x^2 - 18 = 0

2 x^2 - 18 = 2 (x^2 - 9):

2 (x^2 - 9) = 0

Divide both sides by 2:

x^2 - 9 = 0

x = (0 ± sqrt(0^2 - 4 (-9)))/2 = ( ± sqrt(36))/2:

x = sqrt(36)/2 or x = (-sqrt(36))/2

sqrt(36) = sqrt(4×9) = sqrt(2^2×3^2) = 2×3 = 6:

x = 6/2 or x = (-6)/2

6/2 = 3:

x = 3 or x = (-6)/2

(-6)/2 = -3:

Answer: x = 3 or x = -3

User Bert Goethals
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.